PERAN GURU IPS DALAM MENUMBUHKAN SIKAP TOLERANSI SISWA DI SMPN 4 TAROGONG KIDUL - Nining Fitriansyah; Triani Widyanti; Eldi mulyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the role of Social Studies (IPS) teachers in fostering students’ tolerance attitudes at SMPN 4 Tarogong Kidul. The background of this study is based on the observation that some students still show low levels of tolerance, such as forming groups based on similar backgrounds, lack of respect for differences, and the presence of stereotypes in social interactions at school. This research employs a qualitative method with a literature study approach. Data were collected from various sources, including books, scientific journals, and previous studies relevant to the research topic. Data collection was conducted through content analysis, while data analysis involved reviewing, categorizing, and interpreting information based on the research themes. The findings indicate that Social Studies teachers play a strategic role in fostering students’ tolerance through various learning strategies, such as group discussions, problem-based learning, and contextual approaches. In addition, inclusive and democratic pedagogical interactions contribute to the development of mutual respect among students. Supporting factors include a conducive school environment, a curriculum that promotes character education, and teachers’ competence in managing the learning process. Meanwhile, inhibiting factors include external environmental influences, limited teaching methods, and students’ low awareness of the importance of tolerance. In conclusion, Social Studies teachers have a crucial role in shaping students’ character, particularly in fostering tolerance through integrated and meaningful learning processes.